Penerapan Pendekatan Socio-Scientific Issue (SSI) dalam Pembelajaran IPA untuk Meningkatkan Keterampilan Berpikir Kritis Siswa: Tinjauan Pustaka Sistematis - Nida Dusturi; Sabar Nurohman; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2024)
Critical thinking is an ability that students must have in 21st-century learning, especially in science learning. This research aims to analyze the application of the socio-scientific issue approach to improving students' critical thinking skills in science learning. The research method used is a systematic literature review. A systematic literature review was carried out on articles following the research objectives. Articles were obtained using https://sinta.kemdikbud.go.id/ and selected based on criteria from Sinta S1-S3 published in January 2016 – December 2022. A review of the articles found five articles that met the research criteria and assessed the quality of the study. The research results can conclude that applying the socio-scientific issue approach can improve students' critical thinking skills in science learning. The material taught to students using a socio-scientific issue approach includes environmental pollution, environmental change materials, biodiversity, and global warming. The socio-scientific issue approach can be applied to various learning models, such as problem-based learning, group investigation, and problem-solving.